No right to the street: Motorcycle taxis, discourse production and the regulation of unruly mobility. (November 2015) - Qian, Junxi
This article investigates the state regulation of motorcycle taxis in Guangzhou, China. Motorcycle taxis play an important role in sustaining the livelihood of a subgroup of urban migrants. However, this urban informality has become the object of strict state regulation after the use of motorcycle was outlawed by the Guangzhou Municipal Government. This article examines how dominant representations and discourses of motorcycle mobility are implicated in the right to urban streets. On the one hand it argues that both motorcycle mobility and the motorcycle taxi are socially-produced categories made visible and intelligible through the state-led programmes to ground them in a terrain of constructed knowledge. On the other hand, it is contended that the production of ideologically charged representations and knowledge catalyzes and constitutes the spatialisation of state regulatory power. In particular, this article examines the street-level regulatory practices and how these practices restructure both social relations and state power. It indicates that the local police's regulation of motorcycle taxis cannot be sufficiently explained merely in terms of state domination and oppression. Instead, it is anchored in the highly moralised imperative of defending the 'good', the 'ordered' and the 'respectable'.